Accuracy of P0.1 measurements performed by ICU ventilators: a bench study - Beloncle, François (Ann Intensive Care, 2019)
BACKGROUND: Occlusion pressure at 100 ms (P0.1), defined as the negative pressure measured 100 ms after the initiation of an inspiratory effort performed against a closed respiratory circuit, has been shown to be well correlated with central respiratory drive and respiratory effort. Automated P0.1 measurement is available on modern ventilators. However, the reliability of this measurement has never been studied. This bench study aimed at assessing the accuracy of P0.1 measurements automatically performed by different ICU ventilators. METHODS: Five ventilators set in pressure support mode were tested using a two-chamber test lung model simulating spontaneous breathing. P0.1 automatically displayed on the ventilator screen (P0.1(vent)) was recorded at three levels of simulated inspiratory effort corresponding to P0.1 of 2.5, 5 and 10 cm H(2)O measured directly at the test lung and considered as the reference values of P0.1 (P0.1(ref)). The pressure drop after 100 ms was measured offline on the airway pressure–time curves recorded during the automated P0.1 measurements (P0.1(aw)). P0.1(vent) was compared to P0.1(ref) and to P0.1(aw). To assess the potential impact of the circuit length, P0.1 were also measured with circuits of different lengths (P0.1(circuit)). RESULTS: Variations of P0.1(vent) correlated well with variations of P0.1(ref). Overall, P0.1(vent) underestimated P0.1(ref) except for the Löwenstein(®) ventilator at P0.1(ref) 2.5 cm H(2)O and for the Getinge group(®) ventilator at P0.1(ref) 10 cm H(2)O. The agreement between P0.1(vent) and P0.1(ref) assessed with the Bland–Altman method gave a mean bias of − 1.3 cm H(2)O (limits of agreement: 1 and − 3.7 cm H(2)O). Analysis of airway pressure–time and flow–time curves showed that all the tested ventilators except the Getinge group(®) ventilator performed an occlusion of at least 100 ms to measure P0.1. The agreement between P0.1(vent) and P0.1(aw) assessed with the Bland–Altman method gave a mean bias of 0.5 cm H(2)O (limits of agreement: 2.4 and − 1.4 cm H(2)O). The circuit’s length impacted P0.1 measurements’ values. A longer circuit was associated with lower P0.1(circuit) values. CONCLUSION: P0.1(vent) relative changes are well correlated to P0.1(ref) changes in all the tested ventilators. Accuracy of absolute values of P0.1(vent) varies according to the ventilator model. Overall, P0.1(vent) underestimates P0.1(ref). The length of the circuit may partially explain P0.1(vent) underestimation.